Synthesis, Characterization and Study of Antimicrobial Activities of Mannich Bases Incorporating 1,2,4-Triazole Nucleus - Rawat, Rhambus; Deo, Prem Shankar; Shakya, Bhushan (Amrit Research Journal, 2021)
Heterocyclic compounds containing triazole moiety have great importance in the field of medicine, pharmaceuticals, biochemistry, biology, therapeutics, environmental science, and industry. Triazoles and their derivatives have been extensively used in the development of new drugs. Biological activities of Schiff bases are highly investigated, but Mannich bases are on the verge of their development, and they are being synthesized in large number nowadays. In this work, Mannich bases are synthesized by incorporation 1,2,4-triazole moiety through Schiff base using different amines. Mannich bases are found to exhibit highly effective antibacterial and antifungal activities. The formation of synthesized compounds - 1,2,4-triazole-5-thione, Schiff base (4) and Mannich bases (5a and 5b) - are confirmed and characterized by spectroscopic techniques like UV, FTIR 1H-NMR and 13C-NMR. The activity of the synthesized compounds was tested against bacterial and fungal strain.